Evaluasi Penganggaran Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi: Kebijakan Program Kampus Merdeka Tahun 2020 dan 2021 - Syifa Annisa Yaniar; Naufal Bariq Alauddin Simamora; Sansan Febriyanti Kosasih; Daun Putih Anwar (Program Studi Imu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Timor, 2022)
Technological progress is evidence of the times or globalization, and the occurrence of an education crisis is one proof of the impact of the Covid-19 Pandemic. Indonesia's education budget has also increased every year to suit the needs of students and teaching staff in Indonesia. This study uses a qualitative method based on the official website of the Ministry of Education and Culture, Research and Technology, sources of journals and books. In addition, the approach in this study uses Grindle Policy Implementation Theory and Performance-Based Budgeting Theory to see the effectiveness of the implementation and evaluation of the Merdeka Campus Program in 2020 and 2021. The author uses a case study of Kampus Merdeka Program 2020 and 2021 which also involves the role of policy makers both from internal and external of the Ministry of Education, Culture, Research, and Technology. Kampus Merdeka Program has excellent programs in 2020 and 2021 in encouraging the birth of high quality human resources. The author hopes that readers will think more critically about the implementation of the Kampus Merdeka Program after reading this paper.